“The coherence of the text” in sixteenth-century England: Reading literature and law with Abraham Fraunce - Hetherington, M (University of North Carolina Press, 2018)
Abraham Fraunce has long been recognized as an important participant in the literary culture of the 1580s and 1590s, an early reader and acquaintance of Philip Sidney, Edmund Spenser, and other Elizabethan writers. His own works span a wide range of humanist disciplines and genres, including neo-Latin drama, English quantitative poetry, mythography, emblems, logic, rhetoric, and legal theory. Some of his less literary pursuits, particularly his work in law and Ramist logic, can seem misguided, eccentric, or hard to reconcile with his poetic interests; but this article reads Fraunce's work as an exemplary Elizabethan attempt to coordinate the varied intellectual arenas in which humanistically trained graduates might be expected to perform. Moreover, it argues that central to Fraunce's thinking was the question of coherence—the coherence of his culture, of his professional identity and practice as a lawyer, and of the literary texts he wrote and read. While Fraunce remains the primary focus, the article draws on a wide range of texts, from ancient rhetoric, biblical exegesis, and humanist dialectic, to trace the history and role of this important category of Elizabethan hermeneutic inquiry and literary experience. Fraunce's varied interests and his committed but speculative attempts to understand their affinities offer us a rich sense of the overlapping disciplinary spaces in which questions central to late Elizabethan literary theory and practice were explored.